Healthy school, healthy teachers: mediating effect of optimism - Borralho, Liberata; Candeias, Adelinda Araújo; de Jesus, Saúl Neves; Viseu, João (Frontiers in Psychology, 2025)
PurposeIn recent decades, we have witnessed a growing deterioration in teachers’ health and wellbeing, which affects the quality of the teaching and learning process and the school as an organization. The school must provide a quality service that ensures student success. For this, it is essential that teachers feel healthy, satisfied, competent, and active in their work environment, maintaining wellbeing, energy, and appreciative relationships. Organizational and personal variables related to positive psychology have been scarcely studied in educational research concerning teachers’ health.MethodologyThis study aimed to understand: (a) the direct relationships between organizational health and the various dimensions of teachers’ health (professional wellbeing, exhaustion, and cognitive, musculoskeletal, and voice disorders); (b) the direct relationship between organizational health and optimism; (c) the indirect effects of optimism on the relationship between organizational health and the various dimensions of teachers’ health. The research protocol was applied online to a sample of 12,104 Portuguese teachers from basic and secondary education. To analyze the data, the mediation model of organizational health on teachers’ health was evaluated using structural equation modeling (SEM), considering the mediating effect of optimism across the entire sample.FindingsThe results confirmed the tested hypotheses. Organizational health is positively associated with optimism, professional wellbeing and negatively associated with exhaustion, cognitive disorders, musculoskeletal disorders, and voice changes. Similarly, optimism shows a positive relationship with professional wellbeing while being negatively linked to exhaustion, cognitive disorders, musculoskeletal disorders, and voice changes. Optimism mediates the relationship between organizational health and the various dimensions of teachers’ health.ConclusionThis study highlights the importance of organizational health in teachers’ health, emphasizing the mediating role of optimism in reducing the negative impacts of school organization on various dimensions of teachers’ health.